Evaluation of Pseudomonas and Trichoderma enriched organic amendment against Alternaria leaf spot of Withania somnifera - PANDEY*, VIBHA (Indian Phytopathology, 2015)
Leaf blight of Ashwagandha (Withania somnifera) is the most prevalent disease in almost all the cultivated areas of the crop. Systemic fungicides and different isolates of Trichoderma spp. were tested for their efficacy against Alternaria alternata under in-vitro conditions. Similarly, bacterial and fungal bioagents were also tested for their compatibility with different cakes. The Trichoderma isolate, Pseudomonas fluorescens and FYM were evaluated individually and incombination, with or without spray of propiconazole, for the management of Alternaria leaf blight under field conditions. The field experiment was conducted in Factorial Randomized Block Design (FRBD) with factor A comprises of spray of propiconazol @ 0.25 per cent and without chemical spray and the factor B of biological combinations incorporated into the soil. Among the fungicides and different isolates of Trichoderma spp., propiconazole and T. viride 3 (TV3) were found as most effective in reducing the growth of the pathogen. The compatibility studies revealed that the FYM was compatible with both T. viride 3 (TV3) and P. fluorescens. The effect of propiconazole spray was statistically superior to without chemical spray on disease suppression. Similarly, the mixture of T. viride 3 (TV3) + P. fluorescens and FYM + T. viride 3 (TV3) equally reduced the disease incidence and increased the dry root and seed yield.